A new genus, three new species, and new records of plant bugs from Korea (Hemiptera: Heteroptera: Miridae: Phylinae: Phylini) - Duwal, Ram Keshari; Lee, Seunghwan (Zootaxa, 2011)
Five genera and seven species of Phylini, including a new genus and three new species are newly recognized in Korea. Orthophylus gen. nov., to accommodate O. yongmuni sp. nov., and Moissonia kalopani sp. nov. and M. yasunagai sp. nov. are described. Four genera: Atractotomoidea Yasunaga, 1999; Moissonia Reuter, 1894; Monosynamma Scott, 1864 and Pseudophylus Yasunaga, 1999, are reported for the first time in Korea. All reported species are diagnosed with illustrations of male and female genital structures and brief notes.